NON MUSLIM SEBAGAI MENTERI TANFIDZI PERSFEKTIF PEMIKIRAN AL-MAWARDI - Mutasir Mutasir (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2018)
This research was written against the background of Thought raised by al-Mawardi as a prominent Muslim thinker in the Middle Ages who allowed non-Muslims or infidels to occupy the post of minister of Tanfidzi. The Minister of tanfidzi is a ministerial position whose job is to assist the caliph in carrying out all the affairs ordered by the caliph without him having autonomous powers. Al-Mawardi's opinion has caused controversy among scholars both in the classical period until the modern era. In this study, it will study and analyze the reasons used by al-Mawardi to allow non-Muslims to serve as minister of tanfidzi.